The role of EIA and weak assessments of social impacts in conflicts over implementation of renewable energy policies. (April 2018) - Larsen, Sanne Vammen; Hansen, Anne Merrild; Nielsen, Helle Nedergaard
Abstract: Environmental Impact Assessment (EIA) is a policy tool implemented worldwide, to secure considerations of environmental and social impacts as well as democratic decision-making processes, when planning large-scale projects. Many EIAs related to implementation of renewable energy (RE) projects are subject to disputes in Europe, including Denmark. Here, some RE projects lead to citizens forming protest groups and authorities abandoning plans. This is a significant obstacle for implementation of RE policies. This paper investigates the role of EIA, specifically the handling of social impacts, in such conflicts. The paper presents a study of cases of RE projects in Denmark, analysed using a framework based on conflict theories. It is found that social impacts of concern to residents are not properly addressed in EIAs. This constitutes a contradiction between the concerns of the public and the focus of assessments and discussions, forming part of the basis for conflict. Additionally, there is a negative perception among residents of the behaviour of authorities and proponents, which contributes to tensions and leads to mistrust and opposition. It is concluded that to mitigate conflicts over future RE projects and improve the implementation of RE policies, specific improvements can be made in the EIA content and processes. Highlights: A number of social issues of concern to the public are not addressed in the EIA's. Part of the conflict is lack of transparency and unequal distribution of benefits. Conflict has evolved from project-specific impact to including politics and process. To avoid conflict dispute-resolution needs to be addressed when designing processes. Arenas should be established to address disagreements and enter negotiations.